Present situation and influencing factors of presenteeism among nurses in China: a cross-sectional multicenter study - Zehua Li; Zongting Luo; Lifang Chen; Lijuan Chen; Yue Chang; Xiaolin Ma; Lan Tao (BMC Nursing)
Abstract Background Due to the nature of their work, nurses are increasingly becoming a high-risk group for presenteeism. However, research on the factors influencing nurses’ presenteeism, particularly psychological detachment, remains limited. This study aims to investigate the current status of nurses’ presenteeism in China, based on the theory of effort-recovery, analyze the factors that affect presenteeism, and provide a theoretical foundation for targeted interventions. Methods A cross-sectional online questionnaire survey was conducted among 1647 clinical nurses from 37 hospitals in Sichuan Province, China, between September and November 2024, using a convenience sampling method. The questionnaire included demographic data, the Stanford Presenteeism Scale, and the Psychological Detachment scale. Results The average presenteeism score among Chinese nurses was (17.01 ± 5.10), with 65.5% reporting high levels of presenteeism. Multiple linear regression analysis revealed that department, gender, job-pay matching, and psychological detachment were significant factors influencing nurses’ presenteeism (P < 0.05). Furthermore, psychological detachment was negatively correlated with presenteeism (r=-0.274, P < 0.01). Conclusion Presenteeism among nurses in China is above the medium level. Hospital administrators should pay greater attention to this issue and implement effective, targeted strategies to mitigate its occurrence. Clinical trial number Not applicable.